Zanesljivost ocenjevanja dizartrije s slovenskim prevodom Frenchay ocena dizartrije-2 - Drljepan, Mateja (Rehabilitacija (Ljubljana), 2021)
Background: Dysarthria is one of the most common communication disorders associated with neurological impairment. In clinical practice it presents more than half of acquired communication disorders. In a preliminary study we assessed the reliability of the Frenchay Dysarthria Assessment-2 (FDA-2). Methods: The test was administrated to 30 healthy adults ranging in age from 18 years to 80 years. Three speech and language therapists assessed them with Frenchay Dysarthria Assessment-2 (FDA-2). Results: Degree of inter-rater agreement was very high, with the exception of one section where it was medium. Degree of agreement for selected tasks was high or very high. Conclusion: The Slovenian translation of the FDA-2 showed high inter-rater reliability. It is a valid tool for further assessment of dysarthria in research and clinical practise.
Keywords: dizartrija; Dysarthria; FOD-2; Frenchay assessment; Frenchay ocena; neurogenic disorders; nevrogene motnje; rehabilitation; reliability; zanesljivost